2019
DOI: 10.1177/0883073819858455
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Versus Symptomatic Idiopathic Intracranial Hypertension in Children

Abstract: Background: Idiopathic intracranial hypertension is a rare neurologic condition characterized by elevated intracranial pressure with normal cerebrospinal fluid analysis and neuroimaging. A subset of pediatric idiopathic intracranial hypertension patients are coincidentally found to have papilledema and elevated intracranial pressure without symptoms (eg, headache, visual blurring, tinnitus). This study aims to investigate the features of asymptomatic pediatric idiopathic intracranial hypertension. Methods: Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
(61 reference statements)
2
21
0
Order By: Relevance
“…Asymptomatic onset is less frequent and it has been reported in children. In these cases, diagnosis is possible due to the incidental finding of a bilateral optic disc swelling on a routine eye examination [ 6 ]. Thus, the ophthalmologist plays an important role making an early diagnosis, as in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asymptomatic onset is less frequent and it has been reported in children. In these cases, diagnosis is possible due to the incidental finding of a bilateral optic disc swelling on a routine eye examination [ 6 ]. Thus, the ophthalmologist plays an important role making an early diagnosis, as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic patients may present specific anatomic or physiologic variances (a greater number of arachnoid granulations or a better cerebrospinal fluid leak, respectively) that allow a more effective compensation of elevated ICP. Moreover, it has been reported that nutritional, electrolyte and hormonal abnormalities exacerbate the pathology, so in patients without decompensated pathologies, the symptomatic onset is less frequent [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were defined as overweight if body mass index was above 25 or body weight was above the 90th percentile, and obese if body mass index was 30.0 or higher, or over the 97th percentile for age. Subsequently, we merged and combined their clinical data with the information retrieved from 15 previous clinical studies published since 2001 3,14 -32 and performed a pooled analysis. In addition to patient’s weight and gender, data that were analyzed for that purpose included the finding of papilledema and the symptoms of headache, vomiting, visual impairment, dizziness, tinnitus, and associated drug therapies regarded as precipitating factors.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 The fact that pseudotumor cerebri syndrome is associated with male gender and normal body mass in children raises the possibility that the underlying mechanisms are different at a younger age. Most previous studies on pediatric pseudotumor cerebri syndrome 14 -32 included only children, which made the comparison between pediatric and adult patients challenging.…”
mentioning
confidence: 99%